Reputation Management in Public Agencies: The Relevance of Time, Sector, Audience, and Tasks. Issue 6 (July 2019) - Christensen, Tom; Gornitzka, Åse
Reputation management or branding is increasingly important for public organizations. Based on organization theory perspectives and reputation management theory, reputation profiles of four agencies—from the financial and education sectors—are compared. The data used were retrieved from the websites of the agencies at two points in time (2006 and 2016). The main results show not only that the performance dimension of the reputation profile is the most prominent but also that it is more balanced with moral and professional dimensions over time. This shows the increasing multiplicity of reputation management, catering to many and diverse internal and external stakeholders.